Applications of date pits in foods to enhance their functionality and quality: A review - Al-Khalili, Maha; Al-Habsi, Nasser; Rahman, Mohammad Shafiur (Frontiers in Sustainable Food Systems, 2023)
Agro-byproducts are substances generated by the bioprocessing industry that may provide functionality and bioactivity when used in foods, health supplements, and bio-composites. Date pits accumulate in very large quantities as a by-product of date processing factories, and they contain valuable bioactive compounds. Date pits and their treated fractions can serve as a cheap additive in food products, providing functionality such as improved composition in terms of fibers, proteins, fat, vitamins, minerals, polyphenols, and antioxidant compounds. Additionally, date pits have been used as a natural preservative, fat replacer, tenderizing agent, hydrocolloid, and emulsifying agent. Their health functionalities include their antioxidant capacity, dietary fiber content, probiotic enhancement through dietary fibers, and the fact that they are caffeine free. This paper begins by presenting the chemical composition of date pits and their functionalities in various food products. The multifunctional roles of date pits when incorporated into food products are subsequently reviewed. In addition, this review focuses on the applications of date pits in many food products, such as coffee and other beverages, baked goods, meat products, dairy products, desserts, spreads, condiments, and other food-related products. However, it is a challenge to achieve the aforementioned functionality by incorporating date pits into food products at high levels.